Changes Adopted in Asian Pediatric Hospitals during the COVID-19 Pandemic: A Report from the Pediatric Acute and Critical Care COVID-19 Registry of Asia - Wong, Judith J. M.; Abbas, Qalab; Anantasit, Nattachai; Shimizu, Naoki; Malisie, Ririe F.; Dang, Hongxing; Xu, Feng; Ong, Jacqueline S. M.; Lee, Pei Chuen; Saito, Osamu; Pon, Kah Min; Ikeyama, Takanari; Jayashree, Muralidharan; Samransamruajkit, Rujipat; Cheng, Yibing; Liauw, Felix; Kurosawa, Hiroshi; Diaz, Audrey A. N.; Gan, Chin Seng; Zhang, Furong; Lee, Jan Hau; Pediatric Acute Critical Care Medicine Asian Network (Journal of Pediatric Intensive Care, 2021)
There is wide variation in the overall clinical impact of novel coronavirus disease 2019 (COVID-19) across countries worldwide. Changes adopted pertaining to the management of pediatric patients, in particular, the provision of respiratory support during the COVID-19 pandemic is poorly described in Asia. We performed a multicenter survey of 20 Asian pediatric hospitals to determine workflow changes adopted during the pandemic. Data from centers of high-income (HIC), upper middle income (UMIC), and lower middle income (LMIC) countries were compared. All 20 sites over nine countries (HIC: Japan [4] and Singapore [2]; UMIC: China [3], Malaysia [3] and Thailand [2]; and LMIC: India [1], Indonesia [2], Pakistan [1], and Philippines [2]) responded to this survey. This survey demonstrated substantial outbreak adaptability. The major differences between the three income categories were that HICs were (1) more able/willing to minimize use of noninvasive ventilation or high-flow nasal cannula therapy in favor of early intubation, and (2) had greater availability of negative-pressure rooms and powered air-purifying respirators. Further research into the best practices for respiratory support are warranted. In particular, innovation on cost-effective measures in infection control and respiratory support in the LMIC setting should be considered in preparation for future waves of COVID-19 infection.
Keywords: novel coronavirus disease 2019; respiratory disease; noninvasive ventilation; mechanical ventilation; infectious disease